Benedict XVI and Gordon Brown: the crisis’ letters Correspondence exchange on the eve of the G20 Summit (Cultura Económica, 2019)
Correspondence exchange between the Pope Benedict XVI and the Prime Minister of Great Britain, Gordon Brown on the eve of the G20 Summit